Predictors of Tracheostomy in Mechanically Ventilated Guillain-Barré Syndrome (GBS) Patients in a Tertiary care Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Patients suffering from Guillain-Barré syndrome (GBS) may frequently develop an acute respiratory failure and need ventilatory support with prolonged mechanical ventilation (MV) and tracheotomy.Objective: The present study was designed to search for factors that could predict the need for prolonged MV and ultimately need of tracheostomy after completion of immune therapy.Methodology: This retrospective study was performed in patients with GBS admitted to the intensive care unit (ICU) of National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2017 to December 2018. The patients were initiated mechanical ventilation within the first week of admission and were received mechanical ventilation for more than 2 weeks. Demographic, clinical, biological and electrophysiological data and times of endotracheal intubation, tracheotomy, and mechanical ventilation weaning were prospectively collected for all patients. Sequential daily neurological testing used standardized data collection by the same investigators all along the study period.Results: A total number of 74 patients were recruited for this study of which 50% cases required tracheostomy; 34(45.9%) patients needed prolonged mechanical ventilation more than 14 days. The mean duration of mechanical ventilation was 20 days. The strongest observed predictors of tracheostomy were muscle weakness, high CSF protein and Plasma exchange and prolonged mechanical ventilation (P value